2018
DOI: 10.1161/jaha.118.009047
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of 30‐Day Readmissions After Acute Venous Thromboembolism in the United States

Abstract: BackgroundVenous thromboembolism (VTE) is the third leading cause of vascular disease and accounts for $10 billion in annual US healthcare costs. The nationwide burden of 30‐day readmissions after such events has not been comprehensively assessed.Methods and ResultsWe analyzed adults ≥18 years of age with hospitalizations associated with acute VTE between January 1, 2010, and December 31, 2014, in the Nationwide Readmissions Database. International Classification of Disease, Ninth Revision, Clinical Modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…Secemsky et al found that 17.5% of patients had readmission to hospital within 30 days of VTE hospitalization. 1 They did not measure utilization of ED, calculate an incidence rate, or follow up patients out to 90 days limiting comparison with our study. We did not have sufficient sample size to examine the distinct effect of the intervention in low health literacy patients.…”
Section: Conclusion and Relevancementioning
confidence: 95%
“…Secemsky et al found that 17.5% of patients had readmission to hospital within 30 days of VTE hospitalization. 1 They did not measure utilization of ED, calculate an incidence rate, or follow up patients out to 90 days limiting comparison with our study. We did not have sufficient sample size to examine the distinct effect of the intervention in low health literacy patients.…”
Section: Conclusion and Relevancementioning
confidence: 95%
“…We created a new cohort using discharge‐level data from all hospitalizations from State Inpatient Databases of geographically dispersed participating states (18‐27 states) 5 . During cohort creation using NRD, we utilized the ICD‐9‐CM codes to identify all hospitalized adults, at least 18 years old, who had a primary diagnosis (DX1) of VTE (PE or DVT) (453.2, 451.1, 451.8, 453.4, 453.8, 453.5, 453.7, 415.1) for the year 2013 to 2014 5 . All cancer patients were identified using ICD‐9, CCS codes or comorbidities in NRD 5 .…”
Section: Methodsmentioning
confidence: 99%
“…5 All cancer patients were identified using ICD-9, CCS codes or comorbidities in NRD. 5 All patients with metastatic disease (CM_METS) were excluded from the cancer cohort. The outcome studied was CDL therapy (ICD-9 88.60, 88.66, 88.69, 39.90, 88.40, 88.43, 88.44, or 88.49 in combination with 99.10).…”
Section: Methodsmentioning
confidence: 99%
“…Another recently conducted study points out the significant cost burden associated with readmission after discharge from an acute VTE hospitalization, especially among patients with serious comorbidities 14 . Using data from the Nationwide Readmission Database, Secemsky et al 14 identified 1,176,335 hospitalizations for acute VTE between January 1, 2010 and December 31, 2014; of the patients hospitalized for acute VTE, 6.2% died during hospitalization; of those who survived, 17.5% had another hospitalization (for any cause) within 30 days; of those with a readmission, 8.1% died.…”
Section: Potential Predictors Of Vte-related and Vte (Primary Diagnosmentioning
confidence: 99%